Kashmir and it's people : studies in the evolution of Kashmiri society - Kaw, M. K., 1941-; Kashmir Education, Culture, and Science Society (New Delhi : A. P. H. Publishing, 2004)
Contributed articles on civilization of Jammu and Kashmir, India early presented at two seminars
Keywords: Jammu and Kashmir (India) -- Civilization -- Congresses